PRODUCT QUALITY CONTROL USING SIX SIGMA (DMAIC) METHODS TO MINIMIZE WAST IN BIMA MANDIRI CIGARETTE COMPANY REMBANG, PASURUAN REGENCY - Husen, Muhammad; Gustopo, Dayal; Laksmana, Dimas Indra (Lembaga Penelitian dan Pengabdian Masyarakat, Institut Teknologi Nasional (ITN) Malang, 2021)
Quality is a key to be able to compete in the industrial world [16. Quality control is needed to reduce the number of defective products produced by the company, thus reducing losses experienced by the company. The Bima Mandiri Rembang Pasuruan cigarette company is a company that produces cigarettes, one of which is INNO cigarettes. The number of defective products produced by the company so that the company must make an increase in quality by using a method to reduce the number of defects that occur. The number of defective products causes the company to suffer losses. For that, we need a method that can reduce cigarette defective products which in turn can improve the quality of the company's production[12]. Six Sigma with the DMAIC stage (Define, Measure, Analyze, Improve, Control) is a method used in this research. Based on these steps, defects that often occur are less dense cigarettes as many as 289 sticks with a percentage of 25%, tearing on the cigarettes as many as 227 cigarettes with a percentage of 20% and peeling cigarettes as many as 208 sticks with a percentage of 18%. Factors that cause defects include humans, machines, methods and materials. After calculating using the Six Sigma method, before the improvement, the DPMO value is 113988.1 and the Sigma Level value is 2.722. After the improvements were made, the DPMO value decreased to 76488.1 and the Sigma Level was 2.94715. To achieve the six sigma target, the company is expected to be able to carry out improvements with a focus on the factors that cause product defects and always carry out regular control to reduce product defects. The corrective steps taken in the Bima Mandiri Rembang Pasuruan Regency cigarette company are human: regular training for machine operators and employees; methods: inspection of raw materials, blending machines and glue residue in the teat; engine: inspection of engine components; material: reprocessing less refined raw materials and using better quality glue.